Local site effects at the selected stations affected by the February 6 2023 Türkiye Earthquake Sequences - Ilhan, Okan; Indır, Onur; Muratoğlu, Gamze; İçen, Abdullah; Albayrak, Kubilay; Sandıkkaya, M. Abdullah; Askan, Ayşegül; Arduino, Pedro; Taciroğlu, Ertuğrul (Soil dynamics and earthquake engineering (1984), 2024)
This paper explores the applicability of one-dimensional (1D) nonlinear (NL) and equivalent-linear (EL) site response analyses (SRA) for characterizing site effects at selected strong ground motion stations impacted by the February 6, 2023 Türkiye earthquakes. The 1D NL simulations generally underestimate site response at softer sites and for long periods likely due to basin effects and the uncertainties associated with site properties and the 1D approximation. The inclusion of the high-frequency spectral decay parameter (κ0) in 1D simulations decreases the prediction bias of nonlinear SRA, especially at soft sites for short periods. Moreover, the theoretical transfer functions (TTFs) are demonstrated to capture the fundamental site period through in horizontal-to-spectral vertical ratio (HVSR) using ground motion data before and after the February 6, 2023 main event. •The performance of 1D site response approach in capturing site effects at stations affected by 2023 Türkiye events was tested.•1D assumption underestimates the observed PSA for periods greater than site period probably due to basin effects at Hatay.•The use of κ0 to adjust Dmin values of soils was found to slightly reduce the bias in 1D predictions for short periods.•ETFs and TTFs show consistency in the location of peak amplifications while highlighting discrepancies in terms of amplitude.